2006
DOI: 10.1097/00124509-200606000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes Toward Electroconvulsive Therapy Among Health Care Professionals and Students

Abstract: Widespread variations in electroconvulsive therapy (ECT) prescription between and within countries have led many researchers to study professionals' attitudes to the procedure. A questionnaire looking at knowledge and attitudes was administered to 593 medical and nursing students, psychiatrists and anesthetists, and theater and psychiatric nurses. Respondents were based in 2 Irish cities, Dublin and Cork. Poorer knowledge of ECT was found in the nursing group, and this included psychiatric nurses: a third over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
24
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 19 publications
4
24
0
3
Order By: Relevance
“…2,8 This effect has been seen in medical students, but not consistently in students from other professions. 1 Participants' perceptions of other treatment modalities generally did not change significantly between the first and second surveys. This may reflect the fact that most students had no exposure to these modalities during the clerkship.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…2,8 This effect has been seen in medical students, but not consistently in students from other professions. 1 Participants' perceptions of other treatment modalities generally did not change significantly between the first and second surveys. This may reflect the fact that most students had no exposure to these modalities during the clerkship.…”
Section: Discussionmentioning
confidence: 93%
“…In 1 study, most psychiatric nurses surveyed had negative opinions regarding ECT. 1 In a survey of medical graduates and postgraduates, more than half believed that ECT causes brain damage, impairs thinking and reasoning, and is painful and unsafe. In addition, more than 20% believed that ECT is cruel, punitive, or misused.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[35] In an Irish study, 39% of medical students linked ECT to brain damage. [36] A multinational study reported the theoretical knowledge of the Iraqi students to be better than that of both the United Kingdom and Egyptian students. [37]…”
Section: Discussionmentioning
confidence: 99%